2021
DOI: 10.1016/j.bioorg.2021.105024
|View full text |Cite
|
Sign up to set email alerts
|

4-Alkyl-1,2,4-triazole-3-thione analogues as metallo-β-lactamase inhibitors

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 55 publications
2
51
1
Order By: Relevance
“…Its effect might be indirect through its higher rigidity and/or the displacement of water molecules, which would contribute a favorable entropic stabilization energy. [45] Finally, replacing the phenyl ring by a cyclohexyl group (i. e. 50) led to a large decrease in inhibitory potency, confirming the importance of an aromatic group at this position.…”
Section: -49)mentioning
confidence: 91%
See 2 more Smart Citations
“…Its effect might be indirect through its higher rigidity and/or the displacement of water molecules, which would contribute a favorable entropic stabilization energy. [45] Finally, replacing the phenyl ring by a cyclohexyl group (i. e. 50) led to a large decrease in inhibitory potency, confirming the importance of an aromatic group at this position.…”
Section: -49)mentioning
confidence: 91%
“…However, although similar inhibitory activities were measured, this series was of limited interest because these compounds did not behave more favorably in microbiological assays. In parallel, we developed another series of stable compounds possessing diversely substituted alkyl chains at position 4 and found that an alkanoic chain was favourable to VIM‐type MBL inhibition (Figure 1C) [45] . Most importantly, some compounds showed antibiotic potentiation activity on VIM‐producing K. pneumoniae clinical isolates.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,2,4-triazole-3-thione (TZT) derivatives: TZT was identified as a potential motif that interacted with the two zinc ions of MBL (L1) through one of the three nitrogen atoms, and sulfur atom, at the same time. An initial crystal structure evaluation of the analogous compound in complex with the L1 enzyme [132] led to synthesis [133][134][135][136][137][138][139][140] (Scheme 36) and enzymatic inhibition studies on a variety of compounds with variable substituents at positions 4 and 5 of TZT. A number of selected compounds exhibited IC 50 values in the micro-molar range against representative MBLs (i.e., L1, VIM-4, VIM-2, NDM-1, and IMP-1 and CphA); however, limited success was observed in the microbiological assays [134][135][136][137]139,140].…”
Section: 24-triazole-3-thione (Tzt) Derivativesmentioning
confidence: 99%
“…An initial crystal structure evaluation of the analogous compound in complex with the L1 enzyme [132] led to synthesis [133][134][135][136][137][138][139][140] (Scheme 36) and enzymatic inhibition studies on a variety of compounds with variable substituents at positions 4 and 5 of TZT. A number of selected compounds exhibited IC 50 values in the micro-molar range against representative MBLs (i.e., L1, VIM-4, VIM-2, NDM-1, and IMP-1 and CphA); however, limited success was observed in the microbiological assays [134][135][136][137]139,140]. In addition to the antimicrobial activity against class B β-lactamases, a series of compounds was assessed in vitro against KPC-2 as well.…”
Section: 24-triazole-3-thione (Tzt) Derivativesmentioning
confidence: 99%